Biomechanical Motion Analysis of Elite Flat Water Kayakers with Special Focus on Footrest - Kertészné Német, Bernadett; Terebessy, Tamás; Szőke, György; Bejek, Zoltán (Periodica Polytechnica Civil Engineering, 2021)
The purpose of this study was to gain a better understanding of the importance of footrest use and the symmetry of kayaking motions. Method: Measurements were performed on 11 professional male Hungarian kayakers (n = 11), with a mean age of 24 years (range: 18–30 years), a mean height of 184, 5 cm (range: 172–197 cm), and a mean weight of 84 kg (72–96 kg). Weba sport kayak ergometer, Vicon MXT 3D camera system and surface electromyography were used for the measurements. The unique part of the study was the dynamometer, built into the footrest of the ergometer. The right and left sides differed significantly in terms of range of motion in the joints and activity of the muscles involved. Statistically significant differences were observed in the force applied to the footrest between the right and left sides. There were significant differences between the right and left stroke lengths in most athletes. There was a positive correlation between force applied to the footrest, the stroke length and the kayakers’ power output. Our study identified differences and correlations between the parameters of kayaking motion, highlighting the importance of the footrest. Better and more precise footrest use allows correct technique to be applied with high performance.